(untitled) (Historia, 2021)
The current debates concerning land reform with or without compensation; the role of royalty in leadership; curriculum review in South Africa’s basic and higher education fileds and the continued search for personal, regional and national identity are all discussed in this new publication by Phiko Vlelelo and Anne Mager.